Action mode of bacteriocin BM1829 against Escherichia coli and Staphylococcus aureus. (February 2021) - Yan, Hong; Lu, Yingying; Li, Xin; Yi, Yanglei; Wang, Xin; Shan, Yuanyuan; Liu, Bianfang; Zhou, Yuan; Lü, Xin
Abstract: Bacteriocins have potential in the food industry, especially in protecting food safety and controlling food-borne diseases. Class II bacteriocin genes were previously identified from the genome of Lactobacillus crustorum MN047 and successfully expressed in Escherichia coli BL21 (DE3) using the pET-30a system. In this study, the antibacterial mechanism and potential use as a food preservative were studied. The results showed that bacteriocin BM1829 had antimicrobial activity against Gram-positive and Gram-negative bacteria with MIC values of 1–16 mg/L. In addition, BM1829 showed good stabilities to chemicals, and to thermal and pH changes. BM1829 destroyed the integrity of membranes and led to the leakage of cytoplasmic content. Flow cytometry showed that BM1829 arrested the cell cycle at R-phase. Moreover, the number of E. coli and Staphylococcus aureus cells was reduced during beef storage with BM1829 treatment. These data suggested that BM1829 has the potential to be developed as a food preservative or antibacterial agent. Highlights: MIC of BM1829 were 2 and 4 mg/L against E. coli and S. aureus, respectively. BM1829 showed broad-spectrum antibacterial activities and high stability. BM1829 inhibited indicator strains by damaging the integrity of the cell envelope . BM1829 had applications in beef meat preservation.